ANALISIS STABILITAS TIMBUNAN DENGAN MEMBANDINGKAN BRANKAL DAN GEOTEKSTIL - Adhi, Bagas Wahyu; Setiyanto, Beni; Kurniawan, Andri; Pristyawati, Tantin; Rizani, Mohammad Debby (Jurnal Teknik Sipil Giratory UPGRIS, 2023)
Construction activities in road infrastructure development are never separated from earthworks which often become obstacles due to differences in land contours due to excavation and embankment work which is closely related to geotechnical engineering. Embankment and excavation are very interesting things to study because they are closely related to slope safety factors and require special handling. In this research, we examine the use of geotextiles by comparing the handling using safes on embankment stability using PLAXIS Version 8.2 software. The results of embankment stability analysis with safes, settlement at 1 year consolidation was 5.6 cm and settlement at 10 years consolidation was 5.7 cm. in accordance with applicable criteria. The results of the analysis using 2 layers of geotextile showed that the settlement at 1 year consolidation was 4 cm and at 10 years consolidation was 4.1 cm, which is in accordance with the applicable criteria.. Meanwhile, the results of the slope safety factor using bract treatment at 1 year consolidation were 1.475 and the safety factor for 10 year consolidation was 1.478, not in accordance with the design criteria of 1.5. The results of the safety factor using 2-layer geotextile treatment at 1 year consolidation was 1.853 and the safety factor for 10 year consolidation was 1.855, which is in accordance with the design criteria of 1.5.